Bulk organic matter data of Lena Delta permafrost, marine surface sediment, and sediment cores from the Laptev Sea, Arctic Ocean - Tsai-Wen Lin; Gernot Nehrke; Gesine Mollenhauer (PANGAEA, 2025)
To investigate spatial and temporal variations in bulk organic matter characteristics and reactivities, terrestrial and marine sediment samples were analyzed. These samples were obtained from archived collection gathered during previous field campaigns, and include the following types 1) permafrost from the Lena Delta, 2) leachates derived from Lena Delta permafrost, 3) marine surface sediments from the Laptev Sea, and 4) sediment cores PS51/154-11 and PS51/159-10 from the western Laptev Sea. The dataset encompasses a suit of bulk organic matter parameters, including total organic carbon (TOC), carbon to nitrogen ratio (C/N), stable carbon isotope ratio (δ13C), radiocarbon isotope ratio (F14C), labile organic matter content (OML), and refractory and recalcitrant organic matter (OMR) contents.